Eletrofiação de quitosana e poli(óxido de etileno) com incorporação de acetato de itérbio e corantes fluorescentes - Guellis, Crstiane (2019)
Electrospinning is a technique that employs electrostatic forces to produce micro and nanofibers polymer. Therefore, in this work the study of the electrophysics of chitosan (Ch) and poly (ethylene oxide) (PEO) is reported. For this, solutions composed of chitosan and PEO were prepared in aqueous solution of acetic acid 90% v/v, at the concentrations of 1, 2, 3, 4 and 5% w/v, in the proportions of Ch:PEO of 90:10 and 95:05% w/w. For the study of the parameters that influence the electrospinning, tests were performed varying the voltage (kV) form 15, 18, 21 at 23 and the distance from 15, 18 to 20 cm, with the flow maintained constant 0.5 mL h-1. The optimum conditions were concentration of 2% w/v, proportion 90:10% w/w, applied voltage of 18 kV and distance of 18 cm. According to the scanning electron microscopy (SEM) images, the electrospun film in these conditions had an average diameter of 0.2855 ± 0.0508 μm. For the application of the material produced, 2% of the fluorescent dyes acridine orange, erythrosine or fluorescein sodium and 3% of ytterbium III acetate in relation to the mass of the polymers were incorporated. The incorporation of the dyes was confirmed by the spectra of reflectance in the wavelengths close to the maximum absorption of the dyes in solution. Spectrofluorimetry analysis evidenced fluorescence of the material. In the case of ytterbium, proof of incorporation by X-ray fluorescence spectroscopy (FRX) indicated that the mass percentage of this material is 4.4 % of the 3% ytterbium III acetate incorporated in relation to the mass of the polymers. In the characterization of the films by Fourier transform infrared spectroscopy (FTIR), interactions of the chitosan amine group with the components of the blend were observed. In the thermogravimetric analysis (TGA), it was observed, through the comparison with the casting method, a change in the degradation temperature of the polymers according to the method of obtaining the polymer films. In addition, differential scanning calorimetry (DSC) analysis showed that chitosan alters the melting and crystallization temperatures of PEO due to the interaction between the polymers. Finally, with the technique of X-ray diffraction (XRD) it was possible to verify that the films are amorphous.